Effect of Cultural Festivals on the Preservation of Religious Traditions in Immigrant Communities in Nigeria - Oladipo, Olufunke (International Journal of Culture and Religious Studies, 2025)
Purpose: The purpose of this article was to analyze effect of cultural festivals on the preservation of religious traditions in immigrant communities in Nigeria. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Cultural festivals in immigrant communities in Nigeria play a significant role in preserving religious traditions by offering a platform for the transmission of cultural and religious values across generations. These festivals strengthen communal ties, providing opportunities for younger generations to connect with their cultural and religious heritage. Additionally, the festivals foster unity and pride within the community, while helping immigrants maintain their identity in a multicultural society. However, challenges such as modern influences and generational gaps can impact the effectiveness of these festivals in preserving religious practices over time. Unique Contribution to Theory, Practice and Policy: Acculturation theory, social identity theory & cultural transmission theory may be used to anchor future studies on the effect of cultural festivals on the preservation of religious traditions in immigrant communities in Nigeria. By offering teachings on the religious significance of the rituals performed, younger generations can be better equipped to understand and engage with their cultural and religious heritage. Policymakers should consider providing financial support for cultural festivals that play a significant role in the preservation of religious traditions.